The impact of environmental tax, economic growth and renewable energy on CO₂ emissions in Vietnam: Evidence from a VECM approach - Nhung, Le Thi; Nguyet, Bui Thi Minh; Mai, Pham Quynh; Lien, Ha Thi (The Economics and Finance Letters, 2025)
The research assesses the impact of environmental taxes, economic growth, and renewable energy consumption on CO2 emissions in Vietnam during the period 2001-2023. Based on the externality theory, the Environmental Kuznets Curve, and sustainable development theory, the study constructs a Vector Error Correction Model to analyze the dynamic relationships between variables in both the short and long term. The test results indicate that all data series are stationary after first-order differences, with between one and four cointegration relationships among the variables. Empirical analysis reveals that, in the long run, environmental taxes and renewable energy consumption have positive and statistically significant effects on CO2 emission control, whereas GDP per capita growth exhibits a negative and strong effect. In the short term, only environmental taxes demonstrate an immediate regulatory effect, while GDP and renewable energy do not clearly influence emission control. The error correction coefficient is negative and significant, confirming the existence of a long-term equilibrium adjustment mechanism. Additionally, Granger causality tests show that environmental taxes and economic growth are drivers of CO2 emission behavior. Variance decomposition highlights the dominant role of GDP, while the impact of renewable energy remains limited. Based on these empirical findings, the study proposes policy implications to enhance the effectiveness of tax instruments, promote green investments, expand renewable energy use, and improve policy coordination to control CO2 emissions, thereby supporting sustainable economic development in Vietnam.